Implementing Sustainable Gamification Strategies in Elementary Schools: A Case Study of Digital Transformation and Student Engagement - Iim Fatimah; Indah Susi Irianti; Wahyu Haspri Nur Taryanti; Budi Murtiyasa; Masduki Masduki (Papanda Publisher, 2026)
Digital transformation in elementary education necessitates innovative pedagogical approaches that align with digital-native learners' characteristics, yet traditional instructional models persist despite demonstrating limited effectiveness in fostering student motivation and engagement. This study examined gamification implementation in elementary learning contexts to: (1) analyze implementation patterns, (2) evaluate effectiveness in improving learning outcomes, and (3) formulate adaptive sustainability strategies. Employing a qualitative case study design, data were collected from Muhammadiyah Plus Elementary School, Semarang, through semi-structured interviews with eleven participants (principal, six teachers, four students), systematic classroom observations across twelve sessions, and comprehensive document analysis. Data were analyzed using Miles and Huberman's interactive model with triangulation validation. Gamification integration significantly enhanced student engagement (87% active participation versus 52% in non-gamified contexts) and academic achievement, with particularly pronounced gains among lower-achieving students (+13.2%). Analysis revealed that point systems, badges, challenges, and immediate feedback satisfied psychological needs of competence, autonomy, and relatedness as theorized in Self-Determination Theory. Unexpectedly, competitive leaderboards fostered collaborative peer tutoring rather than individualistic behaviors. Sustainability mechanisms included ongoing professional development, adaptive implementation flexibility, Learning Management System integration, and continuous evaluation. Gamification constitutes an effective elementary education innovation when embedded within supportive institutional ecosystems, addressing pedagogical dissonance between traditional methods and digital-native learner characteristics while requiring comprehensive teacher preparation and context-responsive adaptation.